Impact of Management and Leadership in a Private University in the South of Yucatan, Mexico - Ortiz-Navarro, Juan Carlos (2020)
The objective that this investigation pursues, is to understand the role and impact that the administrative management and leadership executed by the Principal to inculcate an institutional philosophy rich in content in her near team to develop organizational culture oriented to achievement and service. This goal, gave the pretext to use a qualitative and naturalistic investigation, in which the researcher coexisted with clue actors and the university community, realizing semi-structured interviews with the Principal and her near team, as well as, a focus group to bachelor students of diverse knowledge disciplines of a University Campus located at Tekax de Alvaro Obregon, Yucatan, Mexico. Discovering that a correct administrative management with a solid, leadership, congruent with the institutional philosophy of the University had gotten the permanence of the institution in the community.